Effects of Feeding Fermented Medicago sativa (Plus Soybean and DDGS) on Growth Performance, Blood Profiles, Gut Health, and Carcass Characteristics of Lande (Meat) Geese - Li, Hui; Liu, Yang; Wei, Lan; Lin, Qian; Zhang, Zhifei (Frontiers in Physiology, 2022)
The objective was to investigate effects of alfalfa (Medicago sativa Linn) mixed silage fermentation material (AMSFM) on various aspects of growth, function, and carcass characteristics of Lande (meat) geese. Based on a previous study, we used the following AMSFM: 80% Alfalfa + 10% soybean meal + 10% DDGS ensiled for 45 d. Lande geese, n=264, 77 d of age, were randomly allocated into 4 groups with 6 replicates in each group. Control geese were fed a basal diet, whereas experimental groups were fed a basal diet supplemented with 6, 12, or 24% AMSFM. The experiment lasted 21 d. The AMSFM promoted some aspects of growth, with increases (P < 0.05) in leg muscle rate, lean meat rate, muscle protein content, and total energy content of leg muscle, plus concurrent decreases (P < 0.05) in crude fat content and abdominal fat rate in chest muscle. In addition, AMSFM increased (P < 0.05) glutathione content in chest and leg muscles, and serum superoxide dismutase activity, and it reduced (P < 0.05) muscle malondialdehyde content and serum concentrations of triglycerides, total cholesterol, urea and aspartate aminotransferase, consistent with good liver and kidney function. Moreover, AMSFM improved (P < 0.05) ileum morphology. In conclusion, the optimal supplemented rate of AMSFM in meet geese diet (12%) improved immunity and antioxidant status, and enhanced growth performance and carcass characteristics of meat geese.